Nanostructuring of a one-dimensional zinc antimonate electrode material through a precipitation strategy for use in supercapacitors. (9th April 2018) - Balasubramaniam, M.; Balakumar, S.
Abstract : The electrochemical properties of ZnSb2 O6 nanorods consisting of two types of heterovalent metal cations, Zn 2+ and Sb 5+, have been investigated. Abstract : The electrochemical properties of ZnSb2 O6 nanorods consisting of two types of heterovalent metal cations, Zn 2+ and Sb 5+, have been investigated. A significant specific capacitance of 53.3 F g −1 was achieved and the nanorods were found to be phenomenally stable, with a capacitance retention of 103.5%. The ZnSb2 O6 nanorods are proposed to be a suitably active electrode material for use in supercapacitors.